2011
DOI: 10.1016/j.fct.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee-collected pollen from five Portuguese Natural Parks: Palynological origin, phenolic content, antioxidant properties and antimicrobial activity

Abstract: a b s t r a c tThe aim of this study was to determine the palynological origin, phenolic content, antioxidant and antimicrobial properties of pollen from five Portuguese Natural-Parks [Parque Nacional Peneda Gerês (PNPG); Parque Natural do Montesinho (PNM); Parque Natural do Alvão (PNA); Parque Natural da Serra da Estrela (PNSE) and Parque Natural do Douro Internacional (PNDI)]. Eight families were found in the mixture of bee pollen: Rosaceae, Cistaceae, Boraginaceae, Asteraceae, Fagaceae, Ericaeae, Myrtaceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
205
7
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 27 publications
24
205
7
13
Order By: Relevance
“…The current results support the proposal made by Morais et al (2011) on the significant role of the qualitative phenolic composition, aside from the phenolic and flavonoid contents, in determining the antioxidant potentials of plant extracts.…”
Section: )supporting
confidence: 91%
See 1 more Smart Citation
“…The current results support the proposal made by Morais et al (2011) on the significant role of the qualitative phenolic composition, aside from the phenolic and flavonoid contents, in determining the antioxidant potentials of plant extracts.…”
Section: )supporting
confidence: 91%
“…High correlations between the kinetic behavior of antioxidant assays and the phenolic and flavonoid contents, and unclear associations between the antioxidant activities and the phenolic and flavonoid contents in different samples have also been found by other authors (Morais et al, 2011). The current results support the proposal made by Morais et al (2011) on the significant role of the qualitative phenolic composition, aside from the phenolic and flavonoid contents, in determining the antioxidant potentials of plant extracts.…”
Section: )supporting
confidence: 80%
“…The correlation between the phenol content in a given sample and the antioxidant activity is, at present, a controversial issue, since while authors like Dobre et al (2011) have been able to establish that correlation, some others like Negri et al (2011) have reported no correlations between these two parameters. Our results agree with those reported by Morais, Moreira, Feás, and Estevinho (2011), who did not find a strong relation between phenol content and antioxidant capability. Synergic or antagonistic effects among phenols, or compounds of different chemical nature, as the result of a particular chemical composition, could be defining the antioxidant properties in such a way that not only the phenol concentration is determinant.…”
Section: Total Antioxidant Capacitysupporting
confidence: 69%
“…As bee pollen contains all the essential amino acids required for the human organism, it is referred to as 'the only perfectly complete food' (7). Notwithstanding, there are only few papers published on the FA composition of the bee bread.…”
Section: Introductionmentioning
confidence: 99%